2015
DOI: 10.3892/or.2015.4410
|View full text |Cite
|
Sign up to set email alerts
|

JQ1, an inhibitor of the epigenetic reader BRD4, suppresses the bidirectional MYC-AP4 axis via multiple mechanisms

Abstract: Bromodomain and extra-terminal domain (BET) family proteins are representative epigenetic modulators that read acetylated lysine residues and transfer cellular signals. Recently, the BET protein inhibitor JQ1 was developed and has been extensively studied in many cancer cell types. We demonstrated that JQ1 effectively suppressed the MYC-AP4 axis and induced antitumorigenic effects by targeting a bidirectional positive loop between MYC and AP4 which was first proposed in the present study. MYC and AP4 are the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…JQ1, a BET bromodomain inhibitor, has been shown to target the epigenetic “reader” thereby playing critical roles in transcriptional elongation and cell cycle regulation [Kanno et al, ]. In addition, JQ1 has been demonstrated to exert anti‐cancer effects both in vitro and in vivo via c‐Myc‐dependent and c‐Myc‐independent manners [Lee et al, ; Choi et al, ]. In this connection, we here demonstrated that JQ1 inhibits the growth of chondrosarcoma cells by the induction of G0/G1 cell cycle arrest, cell senescence, and apoptosis.…”
Section: Discussionsupporting
confidence: 68%
“…JQ1, a BET bromodomain inhibitor, has been shown to target the epigenetic “reader” thereby playing critical roles in transcriptional elongation and cell cycle regulation [Kanno et al, ]. In addition, JQ1 has been demonstrated to exert anti‐cancer effects both in vitro and in vivo via c‐Myc‐dependent and c‐Myc‐independent manners [Lee et al, ; Choi et al, ]. In this connection, we here demonstrated that JQ1 inhibits the growth of chondrosarcoma cells by the induction of G0/G1 cell cycle arrest, cell senescence, and apoptosis.…”
Section: Discussionsupporting
confidence: 68%
“…Previous reports have indicated that ZMYND8 (RACK7) suppresses enhancer overactivation, and ChIP-seq data showed enrichment of enhancer marks (Fig. Then, we treated MCF-7 and ZR-75-1 cells with BRD4 inhibitors (JQ1, OTX015 and CPI-0610) for 24 h, LOL expression was strongly reduced than mock in a dose-dependent manner (except for JQI treatment in ZR-75-1 cells), and the extent of downregulation was greater than that of MYC (a well-known enhancer-regulated gene) [30][31][32] (Fig. 24 In addition, the BET protein BRD4 has been reported to be essential to enhancer activity.…”
Section: Lol Is Transcribed From the Genomic Locus Of An Enhancermentioning
confidence: 97%
“…2d). Then, we treated MCF-7 and ZR-75-1 cells with BRD4 inhibitors (JQ1, OTX015 and CPI-0610) for 24 h, LOL expression was strongly reduced than mock in a dose-dependent manner (except for JQI treatment in ZR-75-1 cells), and the extent of downregulation was greater than that of MYC (a well-known enhancer-regulated gene) [30][31][32] (Fig. 2e).…”
Section: Lol Is Transcribed From the Genomic Locus Of An Enhancermentioning
confidence: 99%
See 1 more Smart Citation
“…BRD binds to MYC and activates enhancer-binding protein 4 (AP4) promoters. AP4 is a key mediator of mitogenicity for proto-oncogene MYC [88]. Upon AP4 activation by MYC, repressing cell cycle arrests gene P21 [88].…”
Section: Bromodomain Inhibitorsmentioning
confidence: 99%